PXMP2 inhibits tumor stemness and immune infiltration in hepatocellular carcinoma based on stemness risk - Dingde Ye; Jiaqing Chen; Jian Wang; Qing Ge; Xianzhong He; Jiamu Qu; Ting Fang; Runze Wang; Shuai Mao; Qiang Wang; Qingxiang Xu; Beicheng Sun (Discover Oncology)
Abstract Background Hepatocellular carcinoma (HCC) is a complex and heterogeneous disease wherein cancer stem cells (CSCs) play a pivotal role in driving tumorigenesis, metastasis, and resistance to therapy. This study sought to map the stemness landscape of HCC and identify patients who may benefit from immunotherapy. Methods A total of 26 stem cell gene sets were obtained from the StemChecker database. A stemness risk model was constructed based on data from TCGA, GEO databases, and bioinformatics methods. The hub genes identified in the model underwent significant preliminary in vitro and in vivo phenotypic validation, which included evaluating their effects on tumor stemness and their functional roles and interactions in TME. This basic verification emphasized the clinical relevance of hub genes and confirmed the practicality of the model in HCC stemness risk assessment and immune infiltration risk assessment, thereby providing a basis for potential treatment strategies. Results HCC patients exhibited three subtypes; C1 showed the worst prognosis, which was linked to high stemness risk and immunosuppressive features. The hub gene PXMP2 demonstrated tumor-suppressive properties by inhibiting tumor stemness in both in vitro and in vivo experiments, promoting the infiltration of anti-tumor M1 macrophages while simultaneously suppressing the infiltration of immunosuppressive M2 macrophages and neutrophils. Moreover, the high expression of PXMP2 was correlated with a favorable prognosis for the patients. Conclusions This study identified three distinct stemness-based subtypes of HCC and established a novel three-gene prognostic risk model. Our findings highlight the critical role of PXMP2 in tumor biology and its potential as a therapeutic target, paving the way for personalized immunotherapy and chemotherapy approaches to enhance clinical outcomes in HCC patients.